DOI: 10.3990/1.9789036549561
|View full text |Cite
|
Sign up to set email alerts
|

Home, but not 'at home' : the reintegration of unskilled Ethiopian female return migrants from Arabian Gulf countries

Abstract: may be reproduced, stored in a retrieval system or transmitted in any form or by any means without permission of the author. Alle rechten voorbehouden. Niets uit deze uitgave mag worden vermenigvuldigd, in enige vorm of op enige wijze, zonder voorafgaande schriftelijke toestemming van de auteur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Based on this theory, migrants return to their country of origin when they have successfully achieved their target earnings, hence, considered a success rather than a failure unlike the neo-classical theory. Nisrane (2020) in his dissertation, cites how De Haas et al (2015) assessed whether return of migrants to their home country is considered a failure based a large survey of Moroccan migrants across Europe or a success as they accomplished their main reason for migration, i.e., financial earnings. They concluded that there is no one theory that can fully explain return of migrants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, migrants return to their country of origin when they have successfully achieved their target earnings, hence, considered a success rather than a failure unlike the neo-classical theory. Nisrane (2020) in his dissertation, cites how De Haas et al (2015) assessed whether return of migrants to their home country is considered a failure based a large survey of Moroccan migrants across Europe or a success as they accomplished their main reason for migration, i.e., financial earnings. They concluded that there is no one theory that can fully explain return of migrants.…”
Section: Introductionmentioning
confidence: 99%